Postnatal Innate Immune Development: From Birth to Adulthood - Georgountzou, Anastasia; Papadopoulos, Nikolaos G. (Frontiers in Immunology, 2017)
It is well established that adaptive immune responses are deficient in early life, contributing to increased mortality and morbidity. The developmental trajectories of different components of innate immunity are only recently being explored. Individual molecules, cells or pathways of innate recognition and signaling, within different compartments/ anatomical sites, demonstrate variable maturation patterns. Despite some discrepancies among published data, valuable information is emerging, showing that the developmental pattern of cytokine responses during early life is age- and TLR-specific, and may be modified by genetic and environmental factors. Interestingly, specific environmental exposures have been linked both to innate function modifications and the occurrence of chronic inflammatory disorders, such as respiratory allergies. As these conditions are on the rise, our knowledge on innate immune development and its modulating factors needs to be expanded. Improved understanding of the sequence of events associated with disease onset and persistence will lead towards meaningful interventions. This review describes the state-of-the-art on normal postnatal innate immune ontogeny and highlights research areas that are currently explored or should be further addressed.